The Need for Safety and the Development of Consumerism in Poland - Pieszak, Eryk (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2014)
The development of consumerism in Poland falls on the last quarter of the century, the transition from controlled economy to free market economy. Elements of the consumer society, in which durables are becoming less and less important and the skillful manifestation of the social position by purchasing fashionable and, simultaneously, symbolic goods that quickly wear out despite their value is becoming more and more important, have reached us before. The essence of the process is that more and more frequently goods should be replaced by subsequent more up¬dated goods-symbols. The position in such an altered society regardless of the country where changes take place depends not on the amount of financial resources but the ability to exchange them for goods of the appropriate meaning. Therefore, in the consumer society one of the driving mechanisms is anxiety and fear connected with the lack of appropriate skills to adjust to changeable conditions.

Rozwój konsumeryzmu w Polsce to okres ostatniego ćwierćwiecza, przejścia od gospodarki sterowanej do gospodarki wolnorynkowej. Oczywiście już wcześniej docierały do nas elementy społeczeństwa konsumpcyjnego, w którym coraz mniej ważne staje się posiadanie trwałych dóbr a coraz ważniejsze staje się umiejętne manifestowanie pozycji społecznej przez zakup modnych i zarazem obdarzonych dużym ładunkiem symbolicznym dóbr, które pomimo swej wartości szybko zużywają się. Istotą procesu jest to, że coraz częściej dobra trzeba zastępować kolejnymi bardziej aktualnymi dobrami-symbolami. Pozycja w takim odmienionym społeczeństwie tak naprawdę niezależnie od kraju w którym się odbywają zmiany zależy nie tyle od ilości zgromadzonych środków finansowych co od umiejętności zamiany ich na dobra o odpowiednim znaczeniu. Dlatego w społeczeństwie konsumpcyjnym jednym z mechanizmów napędowych staje się niepokój a właściwie strach związany z brakiem odpowiednich umiejętności dostosowania się do zmiennych warunków.
Potrzeba bezpieczeństwa a rozwój konsumeryzmu w Polsce